Adaptive fuzzy proportional-integral-derivative control for micro aerial vehicle - Goh, Ming Qian (2021)
With multiple industries employing Micro Aerial Vehicles (MA V) to accomplish various tasks comprising agricultural spraying, package delivery and disaster monitoring, the MA V system has attracted researchers towards resolving its stability issue as emerged from external disturbances. Disruptions caused by both wind and payload change disturbances have prevailed as natural mishaps which degrade performance of the quadrotor MA V system at the horizontal and vertical positions in the aspects of overshoot (OS), rise time (Tr), settling time (Ts)and steady-state error (ess)· Such adversities then cause increased error between the system's desired and actual positions, with a longer rise time and settling time towards reaching its steady-state condition. Adopting the rotary wing quad-rotor MAV system with 'X' configuration as the groundwork, the current study has especially set to explore a new approach for the system's robust positional control in the concurrent presence of wind and payload change disturbances. Earlier literatures have simultaneously suggested the adoptions of linear, nonlinear and hybrid approaches towards handing stability challenge of the quad-rotor MA V. Notably, most hybrid approaches are unable to account for current changes in the system's environment, whilst incapable of concomitantly handle multiple disturbances. An instance being the Fuzzy-PID (FPID) method which merely adjusts the Proportional-Integral-Derivative (PID) gains ensuing discovered positional error from emergence of system's overshoot. Acknowledging such incompetency, this research further proposed Adaptive Fuzzy-PlD (AFPID) controller as the contemporary hybrid approach that includes adaptability function for overcoming nonlinearity of the quad-rotor MA V system, while maintaining the system's robust performance facing current environmental changes from simultaneous wind and payload change disturbances. With the proposed adaptive fuzzy control being adopted to adjust the PID gains in accordance to surrounding changes, undertaken improvement is hereby targeted to eliminate the effect of wind and payload change disturbances amidst stabilizing the employed system. In return, encountered error on both the quad-rotor MA V's horizontal and vertical positions is expected to decline despite concurrent bombardment of multiple external disturbances, following a decrease to the system's overshoot (OS), rise time (Tr), settling time (Ts)and steady-state error (ess). In simulation, performance of the proposed AFPID controller on the horizontal, y position as studied under circumstances of different incoming wind velocities and water flow rates with respect to OS, Tr, Ts and e55 is placed in comparison to the performance of the PID and FPID methods. Improvement is observed in the system's ess for the AFPID controller on the horizontal, y position amid disruption of combined disturbances, with respective reductions of0.93 x 10-3 % and 1.35 X 10-3 % over the performances of PID and FPID controllers. Obtained results then confirm corresponding decline of 27.5% and 21.70% in OS for the AFPID controller over the PID and FPID controllers. A decline of 13 7.50 s and 13.40 s in Ts is further recorded for the AFPID controller as compared to the respective PID and FPID controllers. Accumulated findings, thus, validate AFPID as an effective controller for minimized positional error, smaller overshoot (OS) and steady-state error (esJ, as well as shorter settling time (Ts) and rise time (Tr) as compared to the earlier PID and FPID controllers when faced with uncertain situations of wind and payload change disturbances.